Biocompatibility of metals with osteointegration in bone and dental implants - Gita Gita; Ahyar Ahmad; nurul afdalia adam; Nurmasyita Nurmasyita; Eka Pratiwi Tenriawaru; Harningsih Karim Karim (Universitas Gadjah Mada, 2026)
Permanent metal implants are widely used in dental, cranio-maxillofacial, and orthopedic rehabilitation due to their ability to restore structural integrity and tissue function through osseointegration, which refers to the direct bond between living bone and the implant surface. This review discusses the interaction between implant metal ions and body tissue structures, with emphasis on their effects on bone regeneration, antibacterial activity, and material biocompatibility. The study was conducted through a literature review of major scientific databases, including ScienceDirect, SpringerLink, MDPI, and PubMed. The findings show that implant success is strongly influenced by material biocompatibility, surface topography, and mechanical stability. Metals such as titanium, magnesium, zinc, calcium, silver, and strontium play important roles in supporting osseointegration and biological tissue responses. Magnesium contributes to bone formation by increasing osteoblast activity and inhibiting osteoclasts, while silver and zinc act as antibacterial and anti-inflammatory agents. Calcium and strontium contribute to enhanced osteogenesis and bone mineral density. These developments are expected to improve implant durability, biocompatibility, and patient safety, while opening opportunities for the development of a new generation of biomedical implants that are more intelligent and adaptive.